Use of visual surveys and radiotelemetry reveals sources of detection bias for a cryptic snake at low densities - Boback, Scott M.; Nafus, Melia G.; Yackel Adams, Amy A.; Reed, Robert N. (Ecosphere (Washington, D.C), 2020)
Transect surveys are frequently used to estimate distribution and abundance of species across a landscape, yet a proportion of individuals present will be missed because either they were out of view and unavailable for detection or they were available but not detected because the surveyors missed them. These situations lead to availability and perception bias, respectively, and can result in misleading estimates of abundance and habitat use. In this study, we examined potential biases of visual surveys used for the brown tree snake (Boiga irregularis), a cryptic invasive snake responsible for the extirpation of at least 15 vertebrates on Guam. We simultaneously executed visual surveys and radiotelemetry in a low‐density population of brown tree snakes with two goals in mind: to assess the efficacy of visual surveys in detecting subjects at low densities and to identify sources of perception and availability bias in such surveys. Results indicated that with considerable effort, visual surveys can predict the presence of this cryptic reptile even at low densities (0.4 animals/ha) but perform poorly at predicting areas of high use resulting in inaccurate estimates of relative habitat importance. Telemetered snakes used densely foliated plants including Pandanus tectorius and ferns (epiphytic and terrestrial species) for nearly half of their time, yet <9% of visual survey observations occurred in these microhabitats. Visibility of snakes decreased as they perched higher in the canopy mirroring the disparity between visual survey and telemetry detections but was also surprisingly low near the forest floor (0–1 m). Microhabitats identified in this study are likely to disproportionately affect visual surveys and would be appropriate resources to target for management purposes. When there is critical need to prevent false negatives, such as during an incipient invasion elsewhere, targeted searches of high‐use resources could augment other detection tools to improve detection probabilities of this and other cryptic species.